Pendidikan Anti Korupsi Dalam Budaya Jawa - Daud Eliezar (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2020)
Anti-corruption is the most important part of solving the problem of corruption in Indonesia. Measuring the dimensions of the Anti Corruption Behavior Index (IPAK) shows an interesting phenomenon that is the understanding and assessment of the society tends to be more anti-corruption idealists, on the contrary in practice level when dealing with public services still perform corrupt behavior. Such a public service needs to be found a solution with a sociocultural approach, namely by implementing Javanese cultural values or expressions that are in line with the values contained in the anti-corruption values. Thus the noble values in Javanese culture can make corruption behavior be eliminated. Javanese culture can influence other cultures in carrying out anti-corruption values, where the population distribution is evenly distributed in all provinces in Indonesia. In the end, anti-corruption will become the culture of the Indonesian nation so that it can realize the goals of the Unitary Republic of Indonesia.